2017
DOI: 10.15700/saje.v37n2a1353
|View full text |Cite
|
Sign up to set email alerts
|

Predicting secondary school dropout among South African adolescents: A survival analysis approach

Abstract: Education is one of the strongest predictors of health worldwide. In South Africa, school dropout is a crisis where by Grade 12, only 52% of the age appropriate population remain enrolled. Survival analysis was used to identify the risk of dropping out of secondary school for male and female adolescents and examine the influence of substance use and leisure experience predictors while controlling for demographic and known predictors using secondary, longitudinal data. Results indicated being male, not living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 33 publications
4
59
0
3
Order By: Relevance
“…Prior literature suggests academic disengagement and dropout is associated with risk behavior such as substance use (Townsend et al, 2007) and therefore current results may under-report actual rates of substance use. Previous research has found South African dropouts are 85% more likely to have used tobacco in the past month as compared to non-dropouts (Weybright, Caldwell, Xie, Wegner, Smith, 2016). …”
Section: Discussionmentioning
confidence: 94%
“…Prior literature suggests academic disengagement and dropout is associated with risk behavior such as substance use (Townsend et al, 2007) and therefore current results may under-report actual rates of substance use. Previous research has found South African dropouts are 85% more likely to have used tobacco in the past month as compared to non-dropouts (Weybright, Caldwell, Xie, Wegner, Smith, 2016). …”
Section: Discussionmentioning
confidence: 94%
“…The reasons for youth to leave school are often multidimensional and complex (19). Quantitative South African and international studies have shown that there are multiple reasons for drop out which include poverty (11,20,21), high use of substances (4,5,11,21), bullying (22), boredom (4,23), family needs (helping support the families, being pregnant, traditional family role expectations) (11,19,21,(24)(25)(26), illness (21,27), absenteeism (11,(28)(29)(30), disability (21,26), community violence (21), and school-related factors (academic performance, disliking school, not getting along with teachers, being too old for school and disciplinary consequences) (5,11,19,21,24). In addition, respondents tended to cite nonspecific terms such as "other" reasons for leaving school (27).…”
Section: Reasons For Leaving Schoolmentioning
confidence: 99%
“…Alcohol and tobacco use during adolescence have been associated with school dropout, and poor educational outcomes (4,5,7,8,(32)(33)(34)(35). However, once students drop out of school, their alcohol and tobacco use may vary according to the reason for dropping out.…”
Section: The Relationship Between Reasons For Leaving School and Alcomentioning
confidence: 99%
See 2 more Smart Citations